Otomatisasi Pengontrol Temperatur Suhu Untuk Mesin Pengering Pelet Menggunakan Kontroler Autonics TK4S Dengan Metode PID - Suzantry Handayni, Yanolanda (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2023)
A pellet dryer machine is a tool that makes it easy to dry pellets so it doesn't have to require sunlight to dry the pellets. Various methods have also been widely used to control the temperature on the machine. One of the obstacles experienced is controlling the temperature so that it remains stable and has a good response time. In this journal, a pellet drying machine with PID (proportional integral derivative) method will be designed to keep the temperature stable. The temperature that makes the setpoint is 100 degree C. In the design carried out, it is by comparing sistems that are given Proportional control, Proportional and Integral (PI) control and Proportional Derivative (PD) control. For the controller used, it is an Autonics TK4S type controller. In the control, PID tuning will be carried out which will later be carried out variations of each Kp, Ki, and Kd values.